Collusion Under Risk Aversion and Fixed Costs1. (21st February 2017) - Bernhardt, Dan; Rastad, Mahdi
Abstract : We analyze collusion under demand uncertainty by risk‐averse cartels that care about the utility derived from profits. With sufficient risk aversion and non‐trivial fixed operating costs, it becomes difficult for cartels to collusively restrict output both when demand is low and marginal dollars are highly valued, and when demand is high and potential defection profits are high: output relative to monopoly levels becomes a U‐shaped function of demand. Greater risk aversion or higher fixed operating costs make collusion more difficult to support in recessions, but easier to support in booms.